Sequence-Specific Inhibition Of Microrna-130a Gene By Crispr In Non-Small Cell Lung Cancer Cell Line - Abdollah, Nur Ainina (2019)
Non-small cell lung cancer (NSCLC) is one of the main causes of mortality globally and the incidence has been rising over the years. Current therapies rely on radiation and chemotherapy, which over time exhibited radio-resistance and chemoresistance at the cancer site. Hence, to improve the efficiency and specificity in the cancer therapy, targeted therapeutic strategies based on microRNA (miRNA) are currently being developed. Several studies have reported that miRNA play roles in multi-steps carcinogenesis of cancers, and may serve as potential therapeutic tools for cancer management. Therefore, this study aims to investigate the roles of miR130a in NSCLC by manipulating the expression of miRNA using the clustered regularly interspaced short palindromic repeat (CRISPR)-Cas9 system.